Exploring the potential for internet-based interventions for treatment of overweight and obesity in college students. (December 2015) - Schwartz, Jennifer; Richardson, Chris G.
Objective: To assess the use of internet-enabled technology for seeking health information and resources in overweight/obese college students. Participants: College students ( N = 706) in Vancouver, Canada surveyed in April 2012. Methods: An online survey assessed socio-demographics, health behaviors, and use of internet-enabled technology. Results: Eating habits, dieting and/or exercising to lose weight, and weight satisfaction differed by weight status (all p < 0.05). Of overweight/obese participants, 48% reported they would use online student health resources. When seeking general health information, 91% would use websites; 45% would use online videos; and 75% trusted information from government or health organizations. Conclusions: Overweight/obesity is prevalent among college students. The majority of overweight/obese students reported trying to lose weight and would use the internet for health information, especially if a website is associated with a health organization. The internet is a cost-effective channel for screening coupled with the delivery of tailored, evidence-based interventions for college students.